Evaluation of the effects of Glycyrrhiza glabra and Syzygium aromaticum extracts on gene expression of Streptococcus mutans in patients with dental caries - MAREH L. AL-AMILI; KAMIL M. AL-JOBORI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Al-Amili ML, Al-Jobori KM. 2025. Evaluation of the effects of Glycyrrhiza glabra and Syzygium aromaticum extracts on gene expression of Streptococcus mutans in patients with dental caries. Biodiversitas 26: 418-423. Dental caries, primarily associated with Streptococcus mutans, is among the most widespread diseases, particularly in developing regions such as Iraq. Licorice (Glycyrrhiza glabra) and clove (Syzygium aromaticum) are plants with significant economic value and antibacterial properties that potentially serve as alternatives to chemically synthesized antibiofilm agents. This study aimed to evaluate the antibacterial activity of G. glabra and S. aromaticum extracts against S. mutans and to compare their effects with those of antibiotics, mouthwashes, and toothpaste through gene expression analysis of gtfB and gtfD using RT-qPCR. In total, it did not include the methodology or provide details about the Sub-MIC because it was published separately as a second research study in another journal.100 specimens were collected from patients clinically diagnosed by dental physicians at the Hay Al-Hussein Specialized Center in Maysan City, Iraq. RNA was extracted from dentinal lesion specimens and reverse transcribed into complementary DNA (cDNA). Quantitative polymerase chain reaction (qPCR) was performed to analyze the expression of the gtfB and gtfD genes using the housekeeping gene 16S rRNA as an internal control. The analysis assessed the effects of licorice extract, clove extract, combined extracts, chlorhexidine mouthwash at sub-minimum inhibitory concentration (sub-MIC), and lacalut toothpaste on S. mutans. RT-qPCR results revealed that clove extract significantly reduced the expression of gtfB compared to other treatments, with fold changes of 0.178, 0.454, and 0.191. Licorice extract notably suppressed gtfD expression, with fold changes of 0.215, 0.390, and 0.003 for isolates 74, 80, and 46, respectively. These findings suggest that the plant extracts inhibited specific biofilm-related genes without necessarily reducing the overall bacterial growth. Therefore, these natural extracts can be developed as innovative natural anti-plaque agents.